A questionnaire based survey on knowledge, attitude and behaviour of antibiotic usage and resistance among undergraduates in South Indian teaching hospital - Jayabalan, Nalinidevi; Selvaraj, Nitya; Ganesan, Suganya; Rajamohammad, Meher Ali; Anandan, Isswariya (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Antibiotic resistance has become a global threat in the field of medicine. Multiple causes like antibiotic abuse, irrational usage of antibiotics, over the counter availability of antibiotics etc., have been put forth as culprit leading to antibiotic resistance. The present study aims at evaluating the knowledge, attitude and behaviour of antibiotic usage and resistance among undergraduates in South Indian teaching hospital. Methods: A cross-sectional, questionnaire-based survey conducted in undergraduate MBBS students including 5th to 9th semester at Department of Pharmacology. The questionnaire comprised off: Demographic data; Knowledge including 12 questions using Four-point likert scale; Attitude and behaviours consisting of 8 questions of Yes/No type. Data were analysed in the software SPSS version 24.0. Association among categorical variable were analysed with Analysis of variance (ANOVA) followed by post hoc Bonferroni test. Results: Among 455, 382 students completed the survey instrument and the response rate was 87%. Statistically significant (p=0.002) results have been obtained for the correct responses of knowledge questionnaire. The order of “good knowledge” about antibiotic usage and resistance according to semesters are graded as VIII>VI>V. Unfortunately, there were no significant results seen with attitude and behaviour. Conclusions: The study concluded that, though there was adequate theoretical knowledge among undergraduate students however they lack in their attitude and behaviour regarding antibiotic usage and resistance. Therefore, they need to improve their attitude and behaviour over antibiotic usage and resistance.